An ultra-stable hafnium phosphonate MOF platform for comparing the proton conductivity of various guest molecules/ions. Issue 10 (8th January 2021) - Huang, Yan; Zhou, Fan; Feng, Jianshen; Zhao, Hongxia; Qi, Chao; Ji, Jinyan; Bao, Songsong; Zheng, Tao
Abstract : An ultra-stable PHOS-100(Hf) is reported as an ideal MOF platform for proton conductivity test loading with various guest molecules/ions, as it has excellent chemical and thermal stability. Abstract : A porous hafnium-phosphonate MOF was synthesized using imidazole ionic liquids (ILs), namely PHOS-100(Hf), which has exceptional chemical stability in aqueous environments, even fuming acids. Its rigid framework with permanent porosity makes PHOS-100 an ideal candidate as a platform to fill with different functional guests such as acidic HCl, H2 SO4, or H3 PO4 . The as-synthesized ILs@PHOS-100 exhibits significant humidity-dependent proton conductivities, increasing by four orders of magnitude from 45% RH to 95% RH at 25 °C. After post-treatment with strong acids, the acids@PHOS-100 show enhanced proton conduction at low relative humidities.